Value, Fragment, Narrative: Exploring spoliation in the preservation of built heritage - Axelsson, Nelly (My University, 2023)
Death is a part of being alive. It is a constant reminder of an inevitable ending that every living being experiences. Buildings are no exceptions. Although being inanimate, they are described as having life (S, Cairns & J, Jacobs). The human strive to achieve immortality is rooted in the practice of architecture as well. We try, in various ways, to negotiate the death sentence for buildings through acts of preservation. However, in our fast-paced society, the built fabric is ever-changing, and the challenge is building between the preservation of cultural heritage and future development (Plevoets & Van Cleempoel,). The global environmental challenges are working against our most common strategy which is to “emphasize conservation of the original appearance to a great length of the building chosen as a monument and leave other buildings to be demolished when it faces structural instability or simply goes out of style” (Plevoets, 2022). Social instability and environmental crisis are a call to rethink how we perceive the management of cultural heritage as well as to reduce the climate impact of the building industry. In this context, the ancient method of spoliation can acquire new significance. Spoliation became common during the economic downturn in the late Roman Empire. It entailed removing a part, or fragment, of an antique building on one site and assembling it with other parts on a new site to form a new building (Kinney, 2016). Today, the method of spoliation can offer architects a rich palette of authentic building materials that support storytelling, in connection with raising awareness and contributing to meet global environmental challenges. (Plevoets, 2022) As a response to this call, this thesis seeks to explore the role of the fragment in relation to architectural design and the management of built heritage through the lens of spolia. For the sourcing of materials, as well as for building anew, the thesis will investigate the contemporary landscape of Gothenburg, Sweden. The method relies on three phases: Inventory, design explorations, and project design. Inventory concerns the selective cataloging of elements and materials that can be sourced. Three public buildings in Gothenburg are chosen based on their cultural value. These buildings are explored through various means of drawing: through survey of discrete elements and historical layers, in search of various aspects that have influenced the fragment in its original context. The inventory creates a library of fragments that will be used as spolia in the following steps. The design explorations investigate how the method of spolia could lead to future realities for reused building materials with emphasis on the value of fragments and their abilities to bring forward tangible as well as intangible qualities of the past in a new architectural setting. The project design recognizes spoliation as a method of managing the loss of cultural value and the potential for design. The spolia depository serves as a vessel for the practice of reusing architectural fragments. Within the walls, remnants from demolished buildings accumulate and find new purpose in contemporary designs and constructions.
Keywords: Deconstruction; Reuse of fragments to provoke memory; Storing of fragments; Collection